Conversación dialógica en la clínica de lo psíquico (2012)
ABSTRACT: This paper focuses mainly on the clinical practices addressing psychological issues (psychiatry, family therapy, psychology), as seen from the standpoint of hermeneutics. The hermeneutic approach states that there is currently an ontological change in which human beings are conceived as narrative, relational, and action subjects. This has several implications in the understanding of the clinical practice of psychology: 1) it is conceived as the relationship and encounter between the clinician and the patient; 2) conversation is the axis that articulates this practice; 3) the goal of the clinical practice of psychology is to have patients re-historize themselves, thus building a narrative that allows them to understand their own suffering; and 4) this psychology focuses on the phenomenology of the capable subject, as it promotes the transformation of the patient’s horizon.